The Effect Of Earnings Management, Dividend Policy, And Retained Earnings In Improving The Financial Performance Of LQ45 Companies - Erwin Febriansyah; Karen Jayanti; Rona Naula Oktaviani; Fadrul Fadrul (UNIVED Press, 2026)
This study aims to analyze the influence of earnings management, dividend policy, and retained earnings on the financial performance of companies listed in the LQ45 index on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The research adopts a quantitative approach using panel data regression analysis with the Fixed Effect Model estimation method. The sample consists of 14 companies that consistently appear in the LQ45 index and provided complete financial reports throughout the study period. The results indicate that earnings management, dividend policy, and retained earnings simultaneously have a significant effect on financial performance. Partially, dividend policy and retained earnings have a positive and significant influence, while earnings management does not significantly affect financial performance. These findings highlight the importance of effective dividend and retained earnings management in enhancing a company's financial performance, while manipulative earnings management practices do not contribute meaningfully to sound financial achievement.